The Determinant of Acceptance of SIMDA (Information System of District Management) Implementation on the Government of Batu City - Maksum, Umar; Baridwan, Zaki; Subekti, Imam (Journal of Accounting and Business Education, 2017)
This study aims to examine the factors influencing the acceptability of SIMDA in the Batu Municipal Government. The research model used the Technology Acceptance Model (TAM), which add external construct from D&M success model of information system and other construct namely the commitment of management, social influence and the Individually influence such as computer self-efficacy and personal innovativenes. This research employed census sampling method. The samples are all official of in financial department who use SIMDA. Results of the research showed that perceived usefulness was affected by management commitment, social influence, information quality, system quality, personal innovativeness, and perceived ease of use. In addition, Computer self-efficacy, and personal innovativeness influenced to perceived ease of use. Furthermore, the acceptance SIMDA was influenced perceived usefulness and perceived ease of use. On the contrary, computer self-efficacy did not affect to perceived usefulnessKeywords: Technology Acceptance Model (TAM), Acceptance SIMDA, perceived usefulness, perceived ease of use